Talent management collides with corporate social responsibility: creation of inadvertent hypocrisy. Issue 4 (8th April 2014) - Y. Lacey, Miriam; Groves, Kevin
Abstract : Purpose: – The purpose of this paper is to reveal the unintended effects of talent management (TM) practices on employees excluded from high potential (HiPo) programs. Excluding the majority of employees from the numerous developmental benefits and privileges of HiPo programs runs contrary to the ideals of corporate social responsibility (CSR), an increasingly common espoused value of organizations. This paper discusses the inadvertent hypocrisy of organizations seeking to demonstrate CSR actions for their employees while simultaneously barring the vast majority of employees access to targeted development opportunities. While many organizations are proud of developing exemplary TM systems and executing effective CSR initiatives, further analysis suggests an inherent incompatibility between these approaches as commonly practiced. This paper concludes with a discussion of possible solutions to ameliorate the disconnect between exclusionary TM practices and CSR outcomes. Design/methodology/approach: – Through the theoretical lens of organizational justice, the paper critically reviews relevant research on the impact of TM policies and practices on CSR initiatives. To spur further interest from scholars and practitioners, the paper offers responses to the following questions: What is the usual array of TM practices? What is the organization's social responsibility to its workforce at large and to individual employees? With resources devoted to developing HiPo talent, what is the organization's social responsibility to those in the ranks who have not been identified as HiPo? Findings: – The critical review revealed that organizations seeking to simultaneously pursue TM best practices and CSR initiatives must tackle several fundamental issues, including expanding employee access to HiPo programs, enhancing the HiPo selection processes via greater emphasis on lead indicators of HiPo, and improving rater reliability across assessment tools. The paper concludes with practical suggestions to ameliorate the unintended consequences of disparate treatment of employees by creating a permeable boundary for broader employee inclusion in HiPo programs. Originality/value: – The literature is remarkably deficient in research addressing the effects of TM practices on employees who are excluded from leadership development opportunities, and the resulting implications for CSR outcomes. Given the rapidly growing importance of CSR initiatives for many organizations, research on the impact of TM policies and practices is sorely needed. This paper addresses an important gap in the research literature on the unintended consequences of disparate treatment of employees and offers practical suggestions for more inclusive leadership development systems.